Lacunary Keggin type polyoxotungstates in conjunction with a phase transfer catalyst: an effective catalyst system for epoxidation of alkenes with aqueous H2O2 - Ingle, Rohit H.; Raj, N. K. Kala (Journal of Molecular Catalysis A-Chemical, 2008)
Na-9[SbW9O33] in conjunction with a phase transfer catalyst (methyl tricapryl ammonium chloride) is a highly efficient catalytic system for the selective epoxidation of alkenes with aqueous H2O2 as the oxidant. Importantly, the reactions can be carried out in the absence of any organic solvents. The alkene epoxidation reactions with both, a transition metal ion substituted polyoxotungstate as well as a transition metal ion free polyoxotungstate precursor indicates that the tungstate group is the active center for the oxidation reaction. It was also observed that the transition metal ion does not play any significant role in the reaction. IR studies support the formation of tungsten-peroxo species and also show that the catalyst is stable in the presence of phase transfer catalyst when aqueous H2O2 is used as an oxidant. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alkenes; Aqueous H2O2; epoxidation; Na-9[SbW9O33]; Phase transfer catalyst; polyoxometalates